Implementasi Data Mining Menggunakan Algoritma C4.5 Untuk Memprediksi Penjualan Alat – Alat Telekomunikasi Dan IT (Information Technology) Pada PT Julian Adiputra Utama - Akbar Wijaya; Ahmad Mutatkin Bakti (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
PT Julian Adiputra Utama is a company with expertise in IT and telecommunications (Information Technology). The application of the C4.5 algorithm to classify the level of sales of telecommunication and IT equipment that is often sold to PT Julian Adiputra Utama, is a strategic step to minimize the problems faced by the company, and also PT Julian Adiputra Utama still sells their products by preorder and cannot sell ready stock. for fear that there will be a buildup of stock that will reduce profits for the company. The research method used is descriptive, conducting case study research by reviewing activities in the field, observing and interviewing related parties. The first step in this research is to select the attributes that will be processed in data mining using the rapidminer tool. The KDD method was applied by the authors of this study as a standardization in the data mining process. The source of data in this study is PT that provides sales data information, namely PT Julian Adiputra Utama. The data will be processed with the C4.5 algorithm to find the accuracy results of the data predictions. Keywords— PT Julian Adiputra Utama, Sales, Data Mining, Algorithm C4.5